The Effect of the Treasure Hunt Game Integrated with Think Pair Share Model on Student Activity and Math Learning Outcomes in Fourth Grade - Nur Aissyah; Rasilah Rasilah; Ririn Andriani Kumala Dewi (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This research investigates the influence of a treasure hunt game combined with the Think Pair Share (TPS) learning model on student engagement and mathematics achievement among fourth-grade students at NU Kaplongan Elementary School. The study employed a true experimental design using a pretest–posttest control group approach. The population comprised all fourth-grade students in the 2024/2025 academic year, with participants selected through random sampling. Research instruments consisted of a mathematics achievement test and a student activity questionnaire. Data were analysed using an independent sample t-test to determine differences between the experimental and control groups. Findings revealed a statistically significant improvement in learning outcomes and student activity for the experimental group compared to the control group (t = 2.114, p = 0.03 < 0.05; t = 3.453, p = 0.00 < 0.05). These results support the acceptance of the alternative hypothesis (Ha), indicating that integrating the treasure hunt game with the TPS model effectively enhances mathematics learning at the elementary level. Consequently, this approach is recommended as an innovative strategy combining educational games with collaborative learning to foster active participation and improved academic performance.